2021
DOI: 10.1039/d1cs00074h
|View full text |Cite
|
Sign up to set email alerts
|

Emerging photothermal-derived multimodal synergistic therapy in combating bacterial infections

Abstract: Photothermal therapy (PTT)-derived multimodal synergistic treatments exhibit a super-additive effect in fighting bacterial infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
318
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 500 publications
(318 citation statements)
references
References 235 publications
0
318
0
Order By: Relevance
“…ROS generation is an important factor in SACT-induced cell cytotoxicity, as shown in the previous studies. 48 It has been reported that ROS can oxidize cell membranes, causing damage to DNA, proteins, and lipids. 49 We explored the impacts of free LVFX/encapsulated LVFX on ROS generation under ultrasound stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…ROS generation is an important factor in SACT-induced cell cytotoxicity, as shown in the previous studies. 48 It has been reported that ROS can oxidize cell membranes, causing damage to DNA, proteins, and lipids. 49 We explored the impacts of free LVFX/encapsulated LVFX on ROS generation under ultrasound stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…C3 and C4 nanocomposites eliminated the totality of C. albicans. Therefore, all nanocomposites can eliminate some of the microorganisms used in this study, with C2 being the best, due to its ability to eliminate the three types of microorganisms [113][114][115]. The samples without hydrogel C3 and C4 only presented a complete response in C. albicans, and it could be considered that the photothermic effect allowed microbial elimination, based on the results shown in figure 11c, C3+light and C4+light samples [116].…”
Section: Antimicrobial Effect Of Magnetic Nanocompositesmentioning
confidence: 96%
“…Copyright 2019, ACS Publications antibacterial treatments. The photothermal and magnetocaloric effects of nanozymes can not only decompose biofilms by generating heat to cause thermal damage to bacteria, but also accelerate the release of nanozymes and the generated ROS and enhance the antibacterial activity of nanozymes (Huo et al, 2021;). An antibacterial nanoplatform constructed by encapsulating tungsten sulfide quantum dots (WS 2 QDs) and the antibiotic vancomycin in a thermal-sensitive liposome also showed excellent therapeutic effects on wounds infected by S. aureus due to photothermal therapy, chemodynamic therapy by free radicals and the pharmacological activity of vancomycin (Figure 2a; Xu et al, 2020) In other research, amorphous iron nanoparticles (AIronNPs) with POD-like activity were found to be influenced by an alternating magnetic field, which strengthened the catalytic activity and antibacterial effects of AIronNPs (Figure 2b; Gao et al, 2020).…”
Section: Superficial Woundsmentioning
confidence: 99%